Farm households in Egypt: A typology for assessing vulnerability to climate change - Nin-Pratt, Alejandro; ElDidi, Hagar; Breisinger, Clemens (International Food Policy Research Institute, 2018)
Using governorate-level national data and household survey data, we build a typology of farm households in Egypt that allows us to describe how different farm households behave in response to policy and environmental changes affecting their resources, welfare, and opportunities in output and input markets. One of the major contributions of this study is the building of a unique dataset that combines various data sources at different levels of aggregation, providing the information needed to model the farm typology. We used this dataset as the input of a multi-step procedure that includes the use of principal components and cluster analyses to identify 14 household types. To illustrate possible uses of the typology, we look at the vulnerability of the different types of households to projected changes in temperature, water availability, and water demand from crops due to climate change, and discuss which farmers, production systems, and regions will be most affected by climate shocks. We assumed that increased temperatures by 2050 would result in increased water demand and reduced yields for most crops due to heat stress and harsher growing conditions. We define three climate change scenarios that differ in the expected water flows of the Nile into the Aswan High Dam. Results of simulations using a household model suggest that Egypt is likely to experience a significant reduction in output, agricultural labor demand, and cultivated area because of climate change, although the severity of this outcome will depend on the magnitude of changes in the Nile’s flow. Most affected by these changes will be small and average households producing field crops. Our results suggest that to mitigate the risks and possible future impacts of climate change, the country will need to: Move away from policies supporting production of cereals and water-inefficient crops towards diversification of production into water-efficient high-value crops; facilitate the access of skilled resource-poor producers to capital and markets; and create opportunities for off-farm employment and income for smallholders that are using resources inefficiently.